FACTORS AFFECTING THE COMPETITIVE ENVIRONMENT OF CONSTRUCTION COMPANIES - SOBOLIEVA, TETIANA; NAUMOVICH, JULIA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the tools of competitive analysis and indicators of the construction industry. It is established that currently important external factors in the construction business are factors of indirect influence - economic crises, political factors, including restrictions on imports of raw materials, increased taxes and duties, quarantine restrictions, scientific and technological changes in construction, innovation.Analyzing the trends, we can say that the market of construction services in Ukraine needs to strengthen favorable conditions for development, because over the past 10 years there have been regression trends in the number of construction companies, their financial performance, and despite the fact that the construction services market began to grow 2017-2019, which gave reason to expect future growth of the industry and the improvement of overall performance, quarantine restrictions and crises have again led to a deterioration in the activity and efficiency of the industry. Therefore, the analysis of competition and other factors influencing the formation of competitive behavior of enterprises in an unstable state of the industry require additional research and development of recommendations for their improvement.Based on the analysis of the external and internal environment of construction companies, it can be concluded that the effective functioning of companies, above all, must meet major threats and external challenges such as high competition, constant development of new technologies and emerging competitors, lack of qualified workforce, loss of regular customers. This is possible through the use of the strengths of companies, the realization of external opportunities and overcoming weaknesses. When applying the strategy of leadership in costs, the main areas of improvement of the enterprise should be the development and improvement of technical and technological level of services and products, cost optimization, including by economy on scale. Implementing a differentiation strategy will require improving the range, investing in technology and marketing, finding new suppliers. This will allow companies to enter new market segments, gain new customers and new markets, thus improving competitiveness.
Keywords: competitive environment; competitive analysis; competitive strategy; construction industry